Undocumented students and the policies of wasted potential - Lopez, Janet K., 1976- (New Americans (LFB Scholarly Publishing LLC), 2010)
Lopez?s ethnographic research focuses on college-ready, undocumented high school students and the teacher allies that assisted in these students? attempts to access higher education. She uses North Carolina as a test case. There policies made it difficult, if not financially impossible, for nearly every undocumented student to access college. Despite the academic achievements and resiliency of the undocumented students in the K-12 system, current state and federal policies prohibit undocumented students from pursuing any realistic post-secondary options. Lopez argues that the United States is.